2011
DOI: 10.1051/0004-6361/201015281
|View full text |Cite
|
Sign up to set email alerts
|

Hubbleparameter reconstruction from a principal component analysis: minimizing the bias

Abstract: Aims.A model-independent reconstruction of the cosmic expansion rate is essential to a robust analysis of cosmological observations. Our goal is to demonstrate that current data are able to provide reasonable constraints on the behavior of the Hubble parameter with redshift, independently of any cosmological model or underlying gravity theory. Methods. Using type Ia supernova data, we show that it is possible to analytically calculate the Fisher matrix components in a Hubble parameter analysis without assumpti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 33 publications
1
34
0
Order By: Relevance
“…In other words, data should be able to provide reliable constraints on the behavior of cosmological parameters, running with redshift, independently of any cosmological model or underlying gravity theory. For example, it has been shown that a principal component analysis, adopting SNeIa data, can help to reconstruct the Hubble parameter [17]. This kind of procedure allows to determine H 0 and, in principle, any other cosmographic parameter with reasonable uncertainty and without any ad-hoc parameterizations.…”
Section: Luminosity Distance and Cosmographymentioning
confidence: 99%
“…In other words, data should be able to provide reliable constraints on the behavior of cosmological parameters, running with redshift, independently of any cosmological model or underlying gravity theory. For example, it has been shown that a principal component analysis, adopting SNeIa data, can help to reconstruct the Hubble parameter [17]. This kind of procedure allows to determine H 0 and, in principle, any other cosmographic parameter with reasonable uncertainty and without any ad-hoc parameterizations.…”
Section: Luminosity Distance and Cosmographymentioning
confidence: 99%
“…Even sparser bases that require fewer coefficients for the reconstruction exist, e.g. the principal component basis as introduced in Ishida & de Souza (2011) or Maturi & Mignone (2009). Yet, these approaches are less suitable for our purpose than an analytic basis.…”
Section: Further Numerical Basesmentioning
confidence: 99%
“…tions and the data is used to determine which subset of this basis is better constrained. Then, the function is reconstructed by using this subset [13,17,[20][21][22][23]. Another possibility is to use smoothing methods [24,25].…”
mentioning
confidence: 99%